Transforming emotional pain. (Academic Video Online, 2019)
In an engaging EFT session, Dr. Ladislav Timulak helps the client, Claire, to explore the emotional impact of a very traumatic experience associated with the birth of her daughter. Together, they examine the links between the trauma and the core painful emotions that Claire is experiencing. They also identify and articulate Claire's unmet emotional needs and work to evoke compassionate emotional responses to these needs.